Mycotoxins - Impact and Management Strategies 2019
DOI: 10.5772/intechopen.80363
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins: Their Toxic Effect on Poultry and Recent Advances in Their Treatment

Abstract: About 25% of total agriculture products are contaminated with aflatoxins (AFs) and other mycotoxins in the world especially in Africa, Asia and Latin America, completely losing about 2-3% of food values and thus causing economic losses to farmers. The mycotoxin contaminations of food supply chain impact on human and animal health primarily, whereas production is the second major concern especially in developing countries. Aflatoxins (colorless to pale yellow colored crystals) are the most studied (>5000 resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Feedstuffs containing AFB 1 are often found in broiler farming, which are the basic reasons that reduce the chicken meat quality and profitability (Al‐Shawabkeh et al., 2009 ; Hussain et al., 2010 ). This affects hatchability, chick growth rate, vaccination efficiency, feed intake, growth rate, and susceptibility to diseases in broilers (Sur et al., 2011 ; Ditta et al., 2018 ; Ismail et al., 2020 ). This results in large losses in the broiler farming industry every year.…”
Section: Mode Of Action or Metabolic Mechanism Of Aflatoxin B ...mentioning
confidence: 99%
“…Feedstuffs containing AFB 1 are often found in broiler farming, which are the basic reasons that reduce the chicken meat quality and profitability (Al‐Shawabkeh et al., 2009 ; Hussain et al., 2010 ). This affects hatchability, chick growth rate, vaccination efficiency, feed intake, growth rate, and susceptibility to diseases in broilers (Sur et al., 2011 ; Ditta et al., 2018 ; Ismail et al., 2020 ). This results in large losses in the broiler farming industry every year.…”
Section: Mode Of Action or Metabolic Mechanism Of Aflatoxin B ...mentioning
confidence: 99%
“…Though they are susceptible if toxic diets are fed for extended periods, adult cattle, sheep, and goats are rather resistant to the acute phase of the disease. All examined animal species have demonstrated some degree of vulnerability in experiments (Allah Ditta et al, 2019). Aflatoxin dietary quantities that are often tolerated in animals include dogs, cats, cattle, and weaner pigs, 100 ppb in calves, < 50 ppb in dogs, < 100 ppb in calves, and < 300 ppb in cattle (Jallow et al, 2021).…”
Section: Aflatoxicosis Outbreaksmentioning
confidence: 99%
“…Aflatoxins Highly absorbable (80 to 90%) [74] Induced mild negative effects on the gastrointestinal tract [75] Induced oxidative stress, damaged liver, damaged RNA and DNA, and suppressed immune system [76] Deoxynivalenol Low absorption rate [77] Increased intestinal permeability [ Mycotoxins with high absorption and accumulation rates can remain in edible tissues (meat and liver). Hort et al [93] showed that fumonisins were detected in the liver and fillet muscles.…”
Section: Mycotoxins Absorption Rate In the Gastrointestinal Tract Obs...mentioning
confidence: 99%